2016
DOI: 10.1016/j.envexpbot.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal temperature effects on dormancy influence germination responses to water availability in Arabidopsis thaliana

Abstract: With climate change, germination cuing to water availability is expected to be especially important for seedling survival. Here, we examined germination responses to low water potential and tested whether dormancy status mediates these responses. We considered both genetically based dormancy (genotypes with allelic variation in dormancy genes) as well as dormancy imposed by the environment (low seed-maturation temperature or short duration of dry afterripening). We examined a) germination capacity at low water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…The environment experienced by the mother plant frequently affects germination of the progeny by modifying dormancy levels (Penfield & Springthorpe, ; He et al ., ; Auge et al ., ; Burghardt et al ., ; Edwards et al ., ; Leverett et al ., ). Changes in the maternal environment can do so even if developing seeds themselves do not experience those changes, as observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment experienced by the mother plant frequently affects germination of the progeny by modifying dormancy levels (Penfield & Springthorpe, ; He et al ., ; Auge et al ., ; Burghardt et al ., ; Edwards et al ., ; Leverett et al ., ). Changes in the maternal environment can do so even if developing seeds themselves do not experience those changes, as observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Such 'maternal environmental effects' are well documented in plants (Gutterman, 1982;Donohue & Schmitt, 1998;Donohue, 2009). For instance, in Arabidopsis thaliana, low temperatures experienced before or during seed maturation reduce germination propensity, alter seed responses to chilling and water availability during imbibition, and reduce seed longevity, demonstrating that environmental conditions experienced at one life stage can influence subsequent developmental transitions (Kendall & Penfield, 2012;Penfield & Springthorpe, 2012;Chen et al, 2014;He et al, 2014;Auge et al, 2015;Burghardt et al, 2015;MacGregor et al, 2015;Coughlan et al, 2016;Edwards et al, 2016). These effects of temperature also persist as seeds after-ripen (lose primary dormancy over time) and undergo dormancy cycling (Auge et al, 2015;Burghardt et al, 2015;Edwards et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our results also showed that plant Si contents showed a decline with the MAP (Figure a). The positive correlation between plant Si contents and MAT (Figure b) indicates that increasing MAT may accelerate Si accumulation in plant tissues by promoting soil water availability (Edwards, Burghardt, Zapata‐Garcia, & Donohue, ). At the community level, plant diversity (species richness) and functional group (e.g., grass and legumes) can significantly influence the Si yields of above‐ground biomass in grasslands (Schaller et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal environments can have persistent effects on progeny phenotypes. Some of the maternal effects on seed traits mentioned earlier persisted for several weeks after postdispersal ripening (Burghardt et al ., ; Edwards et al ., ). In Brassica rapa , the maternal competitive environment influenced germination, which later influenced bolting date, leaf length, stem height and internode length (Dechaine et al ., ).…”
Section: When Are Responses To Parental Vs Progeny Environmental Cuesmentioning
confidence: 97%